THE INFLUENCE OF LEARNING COURSE REVIEW HOORAY AND MAKE A MATCH MODEL IN THE LEARNING OF STUDENT OF CLASS X - Wahyu Andriyani; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Education has an important role in improving the quality of learning by implementing efforts to improve it, and it is by this research which is based on learning student learning outcomes by using Course Review Hooray (CRH) learning and make a matching model in class X Students of State Senior High School (SMA Negeri) 1 Sanden, Bantul academic year 2017/2018. This type of research uses comparative research. The population consists of all class X Science Mathematic (MIPA) as many as 112 students are divided into four classes. Sampling was done by a simple random sampling technique and obtained three sample classes, students of class X MIPA 2 as experimental class 1, X MIPA 3 as experimental class 2, and X MIPA 1 as control class with the number of students each class 28 students. The research instrument uses validity and reliability testing. The unreasonable analysis includes the test of normality and homogeneity. Analysis of the data using the anava test. The study results showed differences in mathematics learning outcomes using conventional learning models with Course Review Hooray (CRH) and matching the learning model. It was shown by starting with f_tabe e=3,1093 dan f_count=26,902, which means f_countÂ  of the CRH learning model and make a match with no difference in the result. Learning mathematics rather than conventional learning.